2022
DOI: 10.3389/fmicb.2022.881253
|View full text |Cite
|
Sign up to set email alerts
|

Lobophorin Producing Endophytic Streptomyces olivaceus JB1 Associated With Maesa japonica (Thunb.) Moritzi & Zoll.

Abstract: In this study, we focused on endophytes of Maesa japonica (Thunb.) Moritzi & Zoll. and the plant-microbe interaction at metabolite levels. We isolated seven endophytes associated with M. japonica (JB1−7), and focused on Streptomyces olivaceus JB1 because of antibacterial activities of its secondary metabolites. We confirmed lobophorin analogs production from the bacterial strain JB1 by using spectroscopic techniques such as NMR, UV, and LC/Q-TOF-MS. In the LC/MS system, thirteen reported lobophorin ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Bacteria adapted to high-salinity or acidic environments are prevalent among various halophyte symbionts, where they play crucial roles. , These bacteria attach to the roots or stems of halophytes, either absorbing salt and nutrients or regulating salt concentration, consequently extending the lifespan of the halophytes. In our study of the interaction between endophytes and plants, we isolated a total of nine bacterial strains from the episphere of Suaeda maritima . Among them, YSL2 exhibited the highest antimicrobial activity on agar plates. Furthermore, 16S rRNA analysis of the nine isolated bacteria (YSL1–9) revealed that bacterial strain YSL2 exhibited the highest novelty, sharing 99.5% identity with the closest known species, N .…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria adapted to high-salinity or acidic environments are prevalent among various halophyte symbionts, where they play crucial roles. , These bacteria attach to the roots or stems of halophytes, either absorbing salt and nutrients or regulating salt concentration, consequently extending the lifespan of the halophytes. In our study of the interaction between endophytes and plants, we isolated a total of nine bacterial strains from the episphere of Suaeda maritima . Among them, YSL2 exhibited the highest antimicrobial activity on agar plates. Furthermore, 16S rRNA analysis of the nine isolated bacteria (YSL1–9) revealed that bacterial strain YSL2 exhibited the highest novelty, sharing 99.5% identity with the closest known species, N .…”
Section: Resultsmentioning
confidence: 99%
“…One of the two congeners of hydroxamate siderophores aculeolamides identified in this study was active against Mycobacterium tuberculosis and Plasmodium falciparum but had only negligible cytotoxicity. Um et al (2022) recently described the isolation of several congeners of the spirotetronate macrolide lobophorin from Streptomyces olivaceus JB1, an endophytic actinomycete bacterium from Maesa japonica (broad flat-rock tree). In this case, lobophorins could also be detected in the extracts from the dried leaves of the plant, suggesting that S. olivaceus JB1 could be responsible for the production of these compounds in planta.…”
Section: Bacteri Al Endophy Tes Of Medicinal Pl Ants and Their Second...mentioning
confidence: 99%